Development of Parabolic Motion Learning Devices Based on Technology-Enhanced Guided Inquiry with a Sport Education Approach to Improve High School Students' Critical Thinking Skills - Widi Astutik; Wasis Wasis; Budi Jatmiko; Noer Risky Ramadhani (Universitas Negeri Surabaya, 2026)
Objective: This study aims to develop a parabolic motion learning tool based on a guided inquiry model with a sports education approach to improve the critical thinking skills of high school students. Method: This research is a research and development (R&D) study using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The subjects consisted of 11th-grade high school students involved in both limited and extensive trials. The research instruments included a tool validation sheet, a learning implementation observation sheet, a student response questionnaire, and a critical thinking skills test. Data analysis was conducted using validity, reliability, N-gain, normality, homogeneity, paired t-test, and ANOVA. Results: The results showed that the developed learning tool met the criteria for highly valid with a percentage between 84% and 98%; practical based on the learning implementation category (very good) and student response (87.88%), and effective based on the increase in the N-gain value in the moderate category (0.59–0.62). The statistical test results also showed a significant increase between pretest and posttest scores, and no significant differences between classes, demonstrating the consistent effectiveness of the learning tools. Novelty: The novelty of this research lies in the integration of a guided inquiry model with a sports education approach in physics instruction on parabolic motion to train critical thinking skills through contextual learning based on sports activities, a practice that has not been widely explored in previous research.